Adjustment of the Operational Parameters of an Unconventional Integrated and Illuminated Internally Photobioreactor (ILI-PBR) for the Batch Autotrophic Cultivation of the Chlorella minutissima, Using the Taguchi Method - Amaral, Mateus de Souza; Loures, Carla Cristina Almeida; Silva, Messias Borges [UNESP]; Prata, Arnaldo Marcio Ramalho (Springer, 2020)
Microalgae crops targeting biotechnological applications are conducted in photobioreactors, which allow the adjustment and control of parameters of luminosity, agitation and mixing in the cultivation medium to promote better cell growth and accumulation of metabolites. In this sense, the present work used the Taguchi method to find the best adjustment of the operational parameters of an unconventional photobioreactor denominated internally illuminated integrated photobioreactor (ILI-PBR) with LED light aiming at elevating the biomass concentration, volumetric biomass productivity, and volumetric lipid productivity of Chlorella minutissima microalgae cultivated under autotrophic regime. The effects of the factors were evaluated: illumination (blue, white and red); photoperiod (12 h light:12 h dark, 1 h light:1 h dark, and 24 h clear:0 h dark); aeration (0, 3 vvm, 0.4 vvm, and 0.5 vvm); and recirculation flow rate of cultivation medium (5 L min(-1), 6.5 L min(-1), and 9 L min(-1)) on the variable responses: biomass concentration, biomass volumetric productivity, lipid content, and volumetric lipid productivity. The use of the Taguchi method allowed the increase of biomass concentration, volumetric biomass productivity, and volumetric lipid productivity in the biomass of Chlorella minutissimain 8.6%, 42%, and 143%, respectively, with the adjustment of the operational parameters of the photobioreactor used.
Keywords: Photobioreactor; LED lighting; Taguchi method; Chlorella minutissima; Biomass production